Technology Adoption and Social Innovation: Assessing an Online Financial Awareness Platform - Gasparini, Gian-Luca; Prospero, Aurora; Katmada, Aikaterini; Satsiou, Anna; Konecny, Miroslav; Hanečák, Peter (Internet Science, 2018)
The purpose of this paper is to present the factors that should be taken into consideration when assessing the level of acceptance of an ICT solution by the general public, as well as the innovating impact that such solution is expected to have at the level of society in the European Union. This involves the integration of social and technical skills and expertise, in order to gather the necessary feedback from the users in a clear and concise way. The final goal is to provide an online service that improves the quality of life and work of its users. In order to do so, such service needs to be capable of performing in a way that is as effortless as possible for the user, who will in turn be motivated to use it repeatedly. Moreover, the content of the online service must be able to address a social need in a way that is more efficient and novel than what has been available until then.
Keywords: Mesure de la perception; Réservé UdeM